Starategi pemerintah dan masyarakat dalam meningkatkan wisata arung jeram di paraman Ampalu kecamatan gunung tuleh kabupaten Pasaman barat: Bahasa indonesia - Ratna Ratna; Rozana Eka Putri; Rika Despica (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2025)
This study aims to describe the development strategy of white water rafting tourism in Paraman Ampalu, Gunung Tuleh District, West Pasaman Regency, carried out by the local government, the community, and the Tourism Office. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. Research informants consist of the Tourism Office, local communities, and visitors. The results of the study indicate that 1) The local government has developed Paraman Ampalu white water rafting tourism through guide training, promotion, and cooperation with the community. Basic facilities are available, but signs and location layout still need to be improved. In the future, the focus of development should be on infrastructure, environmental sustainability, security, and supporting facilities to make it more attractive and competitive. 2) Paraman Ampalu management develops white water rafting tourism by utilizing beautiful nature, Pokdarwis involvement, and memorable experiences, while improving human resources, environmentally friendly facilities, and collaboration with the community and the Tourism Office to create an attractive, comfortable, and sustainable destination. 3) The development of white water rafting tourism at this location is carried out by maintaining visitor safety, utilizing the attractive natural atmosphere, developing facilities gradually, and conducting promotions through social media. Community participation is very important for environmental sustainability and improving the quality of tourism in a sustainable manner.